Pemberdayaan Masyarakat Ekonomi Kreatif Kelompok Batik Wanita Sejahtera - Sapta Aji Sri Margiutmo; Maria Magdalena Pur Dwiastuti; Wendri Sukmarani (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
The Special Region of Yogyakarta is one of Indonesia's leading tourist destinations, encouraging the growth of various creative economic sectors, including the souvenir and local craft industries. One community initiative that emerged from this opportunity is the Wanita Sejahtera Batik Group in Muja Muju, Umbulharjo, Yogyakarta. Established in 2023, the group aims to achieve economic empowerment for housewives through traditional batik production, including hand-drawn and stamped batik. However, the group faces several challenges, especially limited access to modern equipment, design innovation, and appropriate technology—factors that hinder the competitiveness of their products in both local and global markets. To address these challenges, capacity building is essential through the implementation of appropriate technology, such as replacing kerosene stoves with electric stoves and using electric canting tools, enabling more efficient and higher-quality production. Additionally, creative design training and product diversification with a focus on sustainability are crucial strategies. One notable innovation is the use of recycled cardboard waste as batik stamping tools, which not only supports environmental sustainability but also adds aesthetic and creative value to the products as part of eco-friendly goods. This innovation strengthens the group's position within the creative economy sector and aligns with market demands that increasingly prioritize sustainable and high-quality products. Through the integration of technological innovation, skill development, and eco-conscious approaches, the Wanita Sejahtera Batik Group has the potential to transform into a highly competitive business player, both nationally and internationally.